Prevalence and Risk Factors of Periodontal Disease During Pregnancy In Indonesia: A Literature Review - Lia Hapsari Andayani; Iwany Amalliah Badruddin; Febriana Setiawati (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Periodontal disease during pregnancy continues to be a significant worldwide health concern with wide-ranging systemic effects. The association between maternal periodontitis and unfavourable pregnancy outcomes (APOs) has been shown by numerous systematic reviews. Studies conducted worldwide reveal significant variations in periodontitis prevalence and associated risk factors. This literature review aims to determine the prevalence and risk factors of periodontal disease during pregnancy in Indonesia. Article searches were conducted in 7 databases: PubMed, ProQuest, ScienceDirect, Scopus, Garuda, EBSCOhost, and Google Scholar. Review: This study followed the predefined PEOS eligibility criteria, with a population consisting of pregnant women of all ages and trimesters in Indonesia, various risk factors associated with periodontal disease as the exposure, and periodontal disease as the outcome. Inclusion criteria were original research published between January 2015 and April 2026, written in English or Indonesian. A total of 312 studies were identified, and 18 studies were included. The reported prevalence of periodontal disease during pregnancy in Indonesia ranged from 4.4% to 100%. Several associated risk factors found are oral hygiene, particularly calculus accumulation, crowded teeth, frequency of toothbrushing, betel nut consumption, smoking status, level of education, living area, gestational age, stress, health motivation, and contraceptive use history. Conclusion: The prevalence of periodontal disease during pregnancy in Indonesia has remained quite high over the past decade. The majority of pregnant women in Indonesia need intervention in the form of Dental Health Education (DHE) and dental scaling.